Requirements for the Application of IFRS 17 in the Iraqi Environment - محمود بكر إبراهيم; الشمري شيماء كاظم (Journal of Economics and Administrative Sciences, 2020)
This research aims to address the most recent international standard in the field of insurance contracts, the International Financial Reporting Standard (IFRS17) and the theoretical framework of the standard in addition to the most important characteristics of the standard (IFRS17), as well as to identify the paragraphs of the modern standard, with the challenges its application in general and the use of the approach (inputs - operations - outputs) to present the challenges of its application in the Iraqi environment and specifically in the environment of Iraqi insurance sector companies (government), the research is based on the main premise that the identification of the requirements for the application of the International Financial Reporting Standard in the insurance companies. The practical aspect was to identify the most important requirements that represent the pillars that help the Iraqi insurance sector companies to adopt the standard and apply it in their companies. The sample was represented by the Iraqi (governmental) insurance companies, the national and Iraqi insurance companies as well as the Iraqi reinsurance company. The researchers reached a number of conclusions, perhaps the most notable: that there is a weakness in the adoption of international standards for financial reporting in the Iraqi environment as well as the absence of a mechanism to move towards the application of the standard (IFRS17), and the researchers recommended a number of recommendations, the most important of which: Iraqi study of the application of IFRS requirements (IFRS17) which will contribute to overcoming the challenges applied locally in the Iraqi environment